Steps toward excellence in neurosurgery - Milena-Monica Ilie; Matei Serban; Alexandru Vlad Ciurea (Romanian Neurosurgery)
The Romanian Society of Neurosurgery (RSN) was founded in 1982 under the leadership of Prof. Dr. Constantin Arsene, with Dr. Ion Oprescu as the society's secretary. This established the first foundational elements for developing organized neurosurgery nationally. Subsequently, especially following the regime change in 1990, SRN experienced significant growth, leading to the 49th Congress. According to the society's statutes, the Congress is held in different locations to involve the entire neurosurgical community in advancing neurosurgery nationwide. The 49th Congress occurred in a remarkable location, Sinaia, known as the "Pearl of the Carpathians" and famed for the splendid Pele? Castle, built by Romania's Royal Family – Carol I of Hohenzollern. The entire Congress was held at the Hotel International, with significant participation from Romania and a notable presence of neurosurgeons worldwide, raising the scientific level of the event. Various neurosurgical topics were structured into substantial sections, including the Young Neurosurgical Corner, dedicated to young neurosurgeons. In conclusion, the 49th Congress, held in English, fully achieved its objective, marking another step forward in the development of this speciality in Romania.